2010
DOI: 10.1111/j.1398-9995.2010.02359.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles are key intercellular mediators in the development of immune dysfunction to allergens in the airways

Abstract: BackgroundPrevious evidence indicates that inhalation of lipopolysaccharide (LPS)-containing with allergens induced mixed Th1 and Th17 cell responses in the airways. Extracellular vesicles (EVs) are nanometer-sized spherical, lipid-bilayered structures and are recently in the public eye as an intercellular communicator in immune responses.ObjectiveTo evaluate the role of EVs secreted by LPS inhalation in the development of airway immune dysfunction in response to allergens.MethodsExtracellular vesicles in bron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 30 publications
0
27
1
1
Order By: Relevance
“…Previous research on BAL MVs has suggested that this MV population has a role in immunity and acts as a conveyor of signals in allergen and infectious immune response 36,37 . Supporting their role in immunity was the finding that BAL MVs are shown to express CD36, which has been implicated in bacterial recognition 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on BAL MVs has suggested that this MV population has a role in immunity and acts as a conveyor of signals in allergen and infectious immune response 36,37 . Supporting their role in immunity was the finding that BAL MVs are shown to express CD36, which has been implicated in bacterial recognition 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in BALF from patients with sarcoidosis, a systemic chronic inflammatory disease predominantly affecting the lung, phenotypically and functionally different vesicles are present compared to healthy individuals [30]. Also intranasal administration of LPS, causing increased infiltration of inflammatory cells and Th1 and Th17 dominated lung inflammation, resulted in quantitative and qualitative changes in the vesicle population isolated from BALF [136].…”
Section: The Role Of Immune Cell-derived Vesicles In Allergic Inflammmentioning
confidence: 97%
“…As described previously, 23 the supernatant was filtered with a 0.22-mm bottle top filter and then centrifuged at 100,000g for 2 hours by using 0.8 and 2.5 mol/L sucrose solutions. After sucrose gradient centrifugation, the interlayer of the 0.8 and 2.5 mol/L sucrose was collected.…”
Section: Isolation Of Evsmentioning
confidence: 99%